Unraveling the Influence of K280 Acetylation on the Conformational Features of Tau Core Fragment: A Molecular Dynamics Simulation Study - Zou, Yu; Guan, Lulu (Frontiers in Molecular Biosciences, 2021)
Abnormal aggregation of the microtubule-associated protein Tau is closely associated with tauopathies, including Alzheimer’s disease and chronic traumatic encephalopathy. The hexapeptide 275VQIINK280 (PHF6*), a fibril-nucleating core motif of Tau, has been shown to play a vital role in the aggregation of Tau. Mounting experiment evidence demonstrated the acetylation of a single-lysine residue K280 in the PHF6* was a critical event for the formation of pathological Tau amyloid deposits. However, the underlying mechanisms by which K280 acetylation affects Tau aggregation at the atomic level remain elusive. In this work, we performed replica exchange molecular dynamics simulations to investigate the influence of acetylation of K280 on the aggregation of PHF6*. Our simulations show that acetylation of K280 not only enhances the self-assembly capability of PHF6* peptides but also increases the β-sheet structure propensity of the PHF6*. The inter-molecular interactions among PHF6* peptides are strengthened by the acetylation of K280, resulting in an increased ordered β-sheet-rich conformations of the PHF6* assemblies along with a decrease of the structural diversity. The residue-pairwise contact frequency analysis shows that K280 acetylation increases the interactions among the hydrophobic chemical groups from PHF6* peptides, which promotes the aggregation of PHF6*. This study offers mechanistic insights into the effects of acetylation on the aggregation of PHF6*, which will be helpful for an in-depth understanding of the relationship between acetylation and Tau aggregation at the molecular level.